PENGARUH TRYOUT DAN UJIAN NASIONAL BERBASIS KOMPUTER TERHADAP SIKAP MENTAL SISWA PADA MTS AL-MAKMUR PARUNGPANJANG - Kartika Mariskhana (Yayasan Akrab Pekanbaru, 2018)
This study aims to determine the try out correlation and computer-based national exams on the mental attitude of MTS Al-Makmur Parungpanjang students. Knowing the correlation relationship try out to the mental attitude of students. Knowing the correlation of computer-based national exam correlation to students' mental attitude The research method used is the method of observation or survey. The sample is 30 students randomly selected from all class IX students, amounting to 300 students at MTs Al-Makmur Parungpanjang. Data collection was carried out by interview techniques, direct observation, questionnaires, and documentation. Data analysis using simple correlation and multiple correlation methods. The statistical test used t test and F test, this study was conducted on March 5, 2018 to April 7 2018. The results showed that the simultaneous try out and national exams gave a positive and significant effect on students' mental readiness at MTs Al-Makmur Parungpanjang. The amount of contribution is 85.6% and the remaining 14.4% is influenced by other factors. While individually try out variable factors can influence the mental attitudes of students in MTs Al-Makmur Parungpanjang proved by using the t test and obtained results of tcount of 0.559 with a significance of 0.581, it can be said that the try out variable can not influence and significantly affect mental students, and individually the national exam variable factors can influence the mental attitudes of students in MTs Al-Makmur Parungpanjang proved by using the t test and obtained tcount of 1.863 with a significance of 0.023, it can be said that the national exam variables can affect and significantly affect the mentality of Al MTs Prosperous Parungpanjang.